2018
DOI: 10.1111/jfs.12563
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological quality of commonly consumed fruit juices and vegetable salads sold in some fruit juice houses in Addis Ababa, Ethiopia

Abstract: This study was conducted by collecting samples of 63 fruit juices and 21 vegetable salads from 21 juice houses. The survey indicated poor kiosk sanitary situation and personal hygiene, and bad storage conditions. Mean average of total viable counts of the samples of juices and vegetable salads was found to be 5.96 log cfu/g. The highest and lowest mean total coliform counts (TCCs) were that of avocado (1.17 log cfu/mL) and mango (0.51 log cfu/mL) juice samples. Mean fecal coliform counts were between 0.04 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
(29 reference statements)
1
19
1
Order By: Relevance
“…About 2.5 billion people, mostly from the LMICs, consume street foods every day [1]. Contaminated fruit and vegetable juices have been reported to be associated with infectious disease outbreaks, producing high morbidity and mortality across the world [2][3][4][5][6]. The World Health Organization (WHO) has reported more than 600 million cases of food-related diseases in the world, resulting in 420,000 deaths and 27,000,000 years of life lost (YLL) [7].…”
Section: Introductionmentioning
confidence: 99%
“…About 2.5 billion people, mostly from the LMICs, consume street foods every day [1]. Contaminated fruit and vegetable juices have been reported to be associated with infectious disease outbreaks, producing high morbidity and mortality across the world [2][3][4][5][6]. The World Health Organization (WHO) has reported more than 600 million cases of food-related diseases in the world, resulting in 420,000 deaths and 27,000,000 years of life lost (YLL) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The tubes with lauryl sulphate tryptose broth (LTB) were inoculated with (10 −1 , 10 −3 , 10 −6 ) diluted samples for 48 h at 35 • C for the TCC and TFC count. In each broth, Durham tubes were inserted to observe the gas formation [39]. After 24 h of incubation, each set of positive tubes that displayed positive acid and gas were counted and calculated using the standard MPN table.…”
Section: Microbiological Analysis Of Fresh Fruit and Vegetablesmentioning
confidence: 99%
“…After 24 h of incubation, each set of positive tubes that displayed positive acid and gas were counted and calculated using the standard MPN table. The positive sample for the completed test was suspended in BGLBB medium at 1 mL and kept at 37 • C at 24-48 h, and the positive results for the tube were determined with the MPN table [39].…”
Section: Microbiological Analysis Of Fresh Fruit and Vegetablesmentioning
confidence: 99%
“…Food safety is another parameter of diet quality that is often overlooked. Nutrient-dense foods, such as fruit, vegetables, dairy, and meat, have in many instances in Ethiopia been found to Sodium intake (g/day) commonly contain high concentrations of microbial pathogens (Amenu et al 2016;Kechero et al 2019;Molla et al 2004). A recent review of evidence from Ethiopia also suggested high food safety risks related to mycotoxins (Ayelign & De Saeger 2020).…”
Section: Figure 20 Average Salt Intake By the Adult Population Of Etmentioning
confidence: 99%